PENGGUNAAN SUMPAH ALLAH SWT DENGAN DZAT-NYA DAN MAKHLUK-NYA DALAM AL-QUR’AN (Studi Ayat-ayat Aqsam dalam Tafsir Al-Mishbah) - dan Maya Herawati, Ilma Amalia, Izzah Faizah Siti Rusydati (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
Aqsam Al-Qur'an is one of the signs in the Al-Qur'an which describes the breadth of knowledge that we can get from every recitation in the verses of the Al-Qur'an. Therefore, one of the functions of the aqsam of the Qur'an is to dispel any doubts within us about the truth conveyed by the great Qur'an. This is the background for the author to examine the use of Allah SWT's oath in the verses of the Qur'an by using His essence and by using His creation. The purpose of this research is to; know the meaning of the aqsam or oath in the Qur'an, know the verses of the oath in the Qur'an that use His substance and know the oath verses in the Qur'an that use His creation. The method used in this study is a qualitative method with a descriptive approach to describe the results of the literature research conducted by the author. The result of this study is that Allah SWT mentions the word qasam 27 times in the Qur'an. However, there are more than 40 verses containing oaths in the Qur'an. The name Allah SWT is used to pronounce vows that are serious and serious threats while for other oaths Allah SWT uses the name of His great and chosen creature. As a conclusion, the author notes that there are more than 40 verses related to the oath of Allah SWT in the Qur'an, while among these verses there are mutually continuous ones between one oath and another so that the author unites the results of the discussion.